Lattice‐based multi‐use unidirectional proxy re‐encryption. Issue 18 (29th June 2015) - Jiang, M. M.; Hu, Y. P.; Wang, B. C.; Wang, F. H.; Lai, Q. Q.
Abstract: Proxy re‐encryption (PRE) is a cryptographic primitive that allows a proxy to turn an Alice's ciphertext into a Bob's ciphertext on the same plaintext. At present, there are many different PRE schemes that have been proposed with different properties. However, all of them are based on the logarithm assumption and the large integer factorization assumption except for a bidirectional PRE scheme over lattices. In this paper, we construct the first multi‐use unidirectional PRE scheme based on lattices. In addition, the generation of the PRE key does not interact with two users, and the scheme can resist collusion attacks. Moreover, it is proved chosen plaintext attack secure in the standard model based on the Learning With Errors assumption. Finally, an identity‐based PRE is obtained from the basic construction. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We construct a first multi‐use unidirectional proxy re‐encryption scheme based on lattices. In addition, the generation of the proxy re‐encryption key does not interact between the two users such that the scheme can be against collusion attack. Moreover, it is proved chosen plaintext attack secure in the standard model based on Learning With Errors assumption and secure in quantum setting. Finally, we extend the basis construction to obtain an identity‐based proxy re‐encryption.